2013
DOI: 10.1016/j.envpol.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial mosses as biomonitors of atmospheric POPs pollution: A review

Abstract: Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. Terrestrial mosses as biomonitors of atmospheric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 77 publications
2
36
0
3
Order By: Relevance
“…In this way, our method allowed correct evaluation of the influence of metal without other major disturbance. However, organic pollutants also accumulated by lichens (Bajpai et al, 2010;Harmens et al, 2013), were not investigated here. By applying the frequencies of studied species to these indices, and comparing to the enrichment factors from Agnan et al (2015), we observed that the four more polluted sites (i.e., HET 54a, EPC 08, CHS 35, and PM 72) as evidenced by bioindication, obtained negative scores (i.e., dominated by resistant lichen species), while several less contaminated sites (e.g., EPC 63 and EPC 74) obtained positive values (i.e., dominated by sensitive lichen species).…”
Section: Resistance and Sensitivity Of Lichen Species To Metal Atmospmentioning
confidence: 99%
“…In this way, our method allowed correct evaluation of the influence of metal without other major disturbance. However, organic pollutants also accumulated by lichens (Bajpai et al, 2010;Harmens et al, 2013), were not investigated here. By applying the frequencies of studied species to these indices, and comparing to the enrichment factors from Agnan et al (2015), we observed that the four more polluted sites (i.e., HET 54a, EPC 08, CHS 35, and PM 72) as evidenced by bioindication, obtained negative scores (i.e., dominated by resistant lichen species), while several less contaminated sites (e.g., EPC 63 and EPC 74) obtained positive values (i.e., dominated by sensitive lichen species).…”
Section: Resistance and Sensitivity Of Lichen Species To Metal Atmospmentioning
confidence: 99%
“…Because moss has no true roots, it takes up nutrients and pollutants primarily from the air and can accumulate them on or in its tissue. 48 Mosses are frequently used as biomonitors to evaluate airborne pollution from POPs. Moreover, the majority of studies have focused on the levels of polycyclic aromatic hydrocarbons (PAHs) in mosses, 49−51 and relatively few studies have been conducted on other POPs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Leucodon sciuroides) was used in this research for method optimization. However, pleurocarpous mosess are very sensitive to pollution and dryness, and therefore are rare, sometimes absent, in urban areas and dry regions [13]. So, acrocarpous mosses, which grow on stone or brick walls and are more commonly used for studying urban environments and dry regions, were also analyzed.…”
Section: Analysis Of Moss Samplesmentioning
confidence: 99%
“…The number of EMEP sites has been gradually increasing over the last few years however, spatial coverage is not sufficient yet. An alternative to conventional precipitation analysis is biomonitoring and mosses are among the organisms most frequently used for this purpose [13]. The moss technique is easier and cheaper than conventional precipitation analysis as it avoids the need for deploying large numbers of precipitation collectors with an associated long-term programme of routine sample collection and analysis.…”
Section: Introductionmentioning
confidence: 99%